Options for states to constrain pricing power of health care providers - Gudiksen, Katherine L.; Murray, Robert B. (Frontiers in Health Services, 2022)
Health care is becoming increasingly unaffordable for both individuals and employers and prices vary in nearly incomprehensible ways that do not correlate with quality. In many areas, consolidation of insurers and providers resulted in market failure that needs policy interventions. With federal gridlock, state policymakers are seeking options for controlling health care costs in markets where competition has failed. In this article, we discuss a spectrum of options that policymakers have to more directly control healthcare prices: (1) establishing a cost-growth benchmark, (2) creating a public option, (3) capping or establishing a default out-of-network payment rate for health care services, (4) creating affordability standards that authorize the insurance commissioner to reject contracts with excessive rate increases, (5) creating global budgets for hospital-based care, (6) capping excessive prices and/or tiering allowed rate updates, and (7) creating a population-based payment model. We provide a roadmap for state policymakers to consider these options, review the experiences with states who have tried these models, and discuss additional design considerations that policymakers should consider with any of these models. In the 1970's and 1980's, during a time of rapid growth in health care prices and spending, states took a decisive leadership role in developing regulatory models to curb the growth in health care costs and improve affordability for their citizens. It is time for states to lead the nation once again in addressing the current health care cost and affordability crisis in the U.S.